ORIENTASI REFORMASI BIROKRASI DALAM MENINGKATKAN PELAYANAN PUBLIK - Sabastiana Desi; Sugeng Rusmiwari (JISIP : Jurnal Ilmu Sosial dan Ilmu Politik, 2016)
Abstract: The bureaucracy role in improving the service quality must be able to fulfill the society need. To get the good service, the official has to be responsible to the customer service. The purpose of this research is knowing the effort of beuraucracy reformation in improving the public service also knowing the supporting and inhibiting factor inside. The ability and the human resource of the bureaucrater is very needed, so that the service orientation reachable gotten. The purpose of this research is knowing the efforts of bureaucracy reformation in increasing the public service and knowing the supportive factors in improving public service. The research used qualitative research. Purposive sampling technique was used in it. The data collecting were observation, interview, documentation. The technique of data anlaysis were data collecting, data reduction, data presentation, conclusion-taking. The data validation was examined through credibility exam by using triangulation technique. The result of the research proved that the effort of bureaucracy reformation in increasing the public service, they were: Increasing the quality of human resource based on the SOP, the welfare giving and fairness toward society, based on the Oprational standard of Public service. Paralyzed with the principles of public government and giving protection and the law assurance. The supported factor of the orientation about bureaucracy reformation in improving the public service based on the Law number 24 the year 2014 concerning to the operational standard of service, the work facility and leader motivation. Keywords: Bureaucration reformation and Public service. Abstrak, Peran birokrasi dalam meningkatkan kualitas pelayanan harus dapat memenuhi kebutuhan masyarakat, agar dapat memperoleh pelayanan yang baik pejabat yang bertugas bisa bertanggung jawab pada tugasnya dalam melayani pelanggan. Tujuan penelitian ini untuk mengetahui orientasi reformasi birokrasi dalam meningkatkan pelayanan publik dan mengetahui faktor pendukung dan penghambat orientasi reformasi birokrasi dalam meningkatkan pelayanan publik. Penelitian ini adalah penelitian kualitatif, teknik penentuan responden menggunakan purposive sampling, teknik pengumpulan data: observasi, wawancara, dokumentasi. Teknik analisis data: Pengumpulan data, reduksi data, penyajian data dan menarik kesimpulan. Keabsahan data diuji melalui uji kredibilitas yaitu dengan menggunakan triangulasi teknik. Hasil penelitian membuktikan bahwa orientasi reformasi birokrasi dalam meningkatkan pelayanan publik mengarah pada peningkatan mutu SDM yang berpatokan pada SOP. Faktor pendukung ialah ketersedian fasilitas kerja dan motivasi pimpinan serta adanya koordinasi antar pegawai yang baik sehingga mampu meningkatkan unsur ketepatan, kecepatan, kesesuaian dan mampu meningkatkan mutu pelayanan yang baik. Faktor penghambat yaitu masih kurang pemahaman warga tentang persyaratan-persyaratan dalam pengurusan surat menyurat, serta adanya hambatan koneksi internet yang berpengaruh terhadap keterlambatan pelayanan. Kata kunci : Reformasi Birokrasi, Pelayanan publik.